Description of a new species of Niphargus (Crustacea: Amphipoda: Niphargidae): the first record of a lake ecomorph in the Carpathian Mountains - Petković, Matija; Delić, Teo; Lučić, Luka; Fišer, Cene (Zootaxa, 2015)
We describe and phylogenetically characterize a new species Niphargus mirocensis from Mt. Miroč, eastern Serbia. This species shows distinct morphology typical for a lake ecomorph of niphargid amphipod, i.e. large and stout body, elongated appendages and raptorial gnathopods and presents the first record of this ecomorph in Carpathian Mountains. Phylogenetic analyses based on Cytochrome Oxidase Subunit 1 gene (COI), Histone (H3) and 28S rRNA (28S) suggests that species is nested within a clade of lake ecomorphs spread in Italy and Central Dinaric Region. The new finding is geographic extension of clade’s range, the species of which are generally narrow endemics.